Digital Transaction for New Economic Transformation of India: Regulatory and Ethical Issues in the Use of AI - Divi, Sriram; Sahoo, Manoj Kumar; Minampati, Venkatram Reddy (Journal of Ecohumanism, 2024)
India is undergoing digital transformation so far as digitalization of payments is concerned. India’s revolutionary payments platforms, online and mobile banking, e-commerce transactions and third-party payments apps have attracted attention of both developed and developing countries. Research methodology adopted is descriptive and based on secondary sources. More than twenty countries have accepted India’s UPI payments platform for digital transactions. Moreover, India is intensively expanding digital penetration in rural areas through Aadhar enabled payments services vie the JAM Trinity i.e. Jan Dhan Accounts, Aadhar citizen identity cards and Mobile data services. Along with all these however, increasing use of Artificial Intelligence (AI) is seen for facilitating all sorts of e-commerce and digital transactions. This throws immense regulatory and ethical issues towards management of AI especially in digital payments and transactions. This paper delves into the current scenario of digital transformation in India and use of AI by different entities. Further this paper explores the ethical and regulatory dimensions of usage of AI in digital transactions. The paper argues the case for urgent development of regulatory mechanism for AI usage in the digital payments spectrum in India and incorporation of ethical issues in it.